Effects of Concomitant Antibiotics Use on Immune Checkpoint Inhibitor Efficacy in Cancer Patients - Jiang, Shuai; Geng, Shuai; Chen, Qian; Zhang, Chen; Cheng, Mengfei; Yu, Yang; Zhang, Shuo; Shi, Ning; Dong, Mei (Frontiers in Oncology, 2022)
Objective Immune checkpoint inhibitors (ICIs) have changed the outcomes of a variety of cancers in an unprecedented manner. Gut microbiome plays a crucial regulatory role in the antineoplastic therapy of ICIs, which can be influenced by antibiotic (ABX) administration. In this efficacy evaluation, we aimed to clarify the correlations of ABX administration with the survival of cancer patients receiving ICIs treatment. Method The eligible literatures were searched using PubMed, Cochrane Library, Web of Science, and Clinical trials.gov databases before Nov 2021. The correlations of ABX administration with progression-free survival (PFS) and overall survival (OS) were determined using Hazard ratios (HRs) coupled with 95% confidence intervals (CIs). Results A total of 12 studies enrolling 6010 cancer patients receiving ICIs treatment were included in this efficacy evaluation. ABX administration was significantly correlated worse PFS（HR=1.60，95%CI=1.33-1.92，P＜0.00001） and OS（HR=1.46，95%CI=1.32-1.61，P＜0.00001）. Similar results were found in the subgroup analysis of non-small cell lung cancer (NSCLC), renal cell carcinoma (RCC) and melanoma. Conclusions ABX use before, during or after ICIs treatment of cancer may significantly shorten PFS and OS. ABX should be used cautiously in cancer patients receiving ICIs. However, further validations are still essential due to existing publication bias.